Diagnosis of Primary Cancer of the Liver. Issue 5784 (13th November 1971) - Kew, M. C.; Dos Santos, H. A.; Sherlock, Sheila
Abstract : The diagnosis of primary cancer of the liver was reviewed in 75 patients. A definitive diagnosis was made during life in 63% and in a further 20% this condition was suspected though histological confirmation was obtained only at necropsy. The most common presenting complaints were abdominal pain and weight loss and the most frequent findings hepatomegaly and ascites. Less than one-half of the patients were jaundiced and when present it was usually mild. An arterial bruit was heard over the liver in 25% of the patients. A sudden and unexplained deterioration in a patient known to have cirrhosis or haemochromatosis should raise the possibility of a primary hepatic tumour; this occurred in 24% of our patients. Alpha-fetoprotein was found in the serum of 11 out of 18 cases. The presence of a mass in the liver was frequently confirmed by liver scan, portal venography, or hepatic arteriography, but these showed no features diagnostic of a primary tumour. Liver scan also proved useful in localizing the lesion for biopsy purposes. Definitive diagnosis is dependent on the histological demonstration of the features of the tumour. This can frequently be achieved by percutaneous needle biopsy, which was positive in 38 out of 57 patients. Wedge biopsies were positive in a further nine patients.